Worth dying for - Child, Lee (New York Delacorte Press, 2010)
In the corn country of Nebraska, ex-police officer Jack Reacher runs afoul of the local Duncan clan--and its criminal connections--when he investigates a decades-old, unsolved case of a missing child.
A Reacher novel
Keywords: Reacher, Jack -- (Fictitious character) -- Fiction; Ex-police officers -- Fiction; Missing children -- Fiction; Nebraska -- Fiction